Methods and means for developing resistance in the 5th and 6th grades - Bitang, Andrei; Monica, Stertl; Andrei, Vasile Liviu Andrei; Dulceanu, Corina; Macarie , Anca (Arena-Journal of Physical Activities, 2022)
Introduction: In all physical education school curricula, starting with the primary cycle and going to high school and vocational school, resistance appears as an educational instructional objective formulated and materialized as a requirement in relation to class, therefore, the age of students (Scarlat E., Scarlat MB, 2002). Purpose: is to implement an experiment in the fifth and sixth grades in rural areas, and through the results obtained from this experiment, to be able to find optimal solutions to equip students with a high vital capacity, given that after school most students help their parents with household chores. Methodology: Resistance is “the ability of the human body to exert efforts with a relatively long duration and a relatively high intensity, maintaining constant indices of optimal effectiveness”. Results: Following the evolution of the arithmetic mean in the endurance running test over the distance of 800m, the boys found that at the initial testing the control group achieved an average of 03:40, and the experiment group achieved an average of 03:29. There is a difference between the control group and the experiment group in favor of the experiment group, namely 11 sec. After the intermediate tests, the control group obtained an average of 03:37, making a progress compared to the initial test by 3 seconds, and the experiment group achieved an average of 03:24. The experiment group made even greater progress thanof the arithmetic mean in the endurance running test over the distance of 600m girls, we found that in the initial testing the control group achieved an average of 03:08, and the experiment group achieved an average of 03:09. There is a difference between the control group and the experiment group in favor of the experiment group, namely 1 sec. After the intermediate tests, the control group obtained an average of 03:01, making a progress compared to the initial test with 7 sec., And the experiment group achieved an average of 03:04 with 5 sec. better than the initial test. We notice that the experiment group made more progress than the control group in the final test, namely 2 sec. Conclusion: this paper emphasizes the importance of the exercises we used and applied to students in the first two grades of high school.